1996
DOI: 10.1093/ajcp/105.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Antral Atrophy,Helicobacter pyloriColonization, and Gastric pH

Abstract: The association between the topographic distribution of Helicobacter pylori colonization, inflammation and atrophy of the gastric mucosa, and fasting gastric pH was studied in a population with high prevalence of multifocal atrophic gastritis. Increasing atrophy of the antrum was associated with decreasing H pylori colonization of the antrum itself, but increasing colonization of the corpus. Advanced atrophy was associated with high fasting gastric pH. However, after therapeutic eradication of H pylori, inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 24 publications
2
35
0
2
Order By: Relevance
“…However, this technique is relatively invasive and is difficult to be routinely performed for all patients with acid-related disorders. For this reason, we measured the pH of gastric juice samples collected by aspiration during endoscopy, as this approach has also been used to evaluate acid secretion [23,24,25]. Using one-point measurements, we found that gastric juice pH was significantly associated with gastric mucosal injury induced by LDA.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique is relatively invasive and is difficult to be routinely performed for all patients with acid-related disorders. For this reason, we measured the pH of gastric juice samples collected by aspiration during endoscopy, as this approach has also been used to evaluate acid secretion [23,24,25]. Using one-point measurements, we found that gastric juice pH was significantly associated with gastric mucosal injury induced by LDA.…”
Section: Discussionmentioning
confidence: 99%
“…This is illustrated by various observations. Firstly, H. pylori corpus gastritis is often associated with hypochlorhydria, and eradication therapy leads to increased acid secretion in these subjects (158,533). Secondly, H. pylori corpus gastritis augments the acid-suppressive effects of PPIs (663).…”
Section: Disease Typesmentioning
confidence: 99%
“…We speculated that eradication may prevent extension of intestinalization even in the high-risk group for gastric cancer. It is reported that CDX2 expression and intestinal trans-differentiation in the gastric mucosa can be suppressed by an increase in acid secretion that often follows H. pylori eradication presumably due to removal of the postulated acid inhibitory factors [29,30,31,32]. Further studies are required to elucidate the molecular mechanisms how eradication suppress aberrant CDX2 expression.…”
Section: Discussionmentioning
confidence: 99%